Keberhasilan Sistem Informasi Dalam Menunjang Efektivitas Penjualan - Sri Dewi Angga; Sandy Nopen Silalahi; Kabidin Kabidin; Yurry Yesaya (Universitas Komputer Indonesia, 2021)
This study aims to find out the effect of internal control on the use of accounting information systems in the company and To find out the amount of success of accounting information systems that can have an impact on sales effectiveness in the company in PIC H1 Rejeki Motor Bandung. This study uses a case study approach. The method of data collection used is to disseminate questionnaires and interviews. The data source used is primary data. Data analysis is done by comparing the reality in the company and the proposed business development carried out with existing theories. Based on data processing that internal control has an influence on the success of accounting information system and also the success of accounting information system has an influence on sales effectiveness. It can be concluded that the discovery of weaknesses such as a low surveillance environment resulted in the accounting information system is still used as a tool to commit fraud. And also still found errors during the data process that resulted in the resulting information is not reliable and also resulted in sales procedures have not run as determined by the company. Key Words : Internal Control, Accounting Information System, Sales Effectiveness